ANTI-INFLAMMATORY AND MYDRIATIC INTRACAMERAL SOLUTIONS FOR INHIBITION OF POSTOPERATIVE OCULAR INFLAMMATORY CONDITIONS - DEMOPULOS GREGORY A; FLORIO VINCENT A (2024)
본 발명은 안과의 외과적 처치 동안 비스테로이드성 항-염증제 및 알파-1 아드레날린성 산동제를 포함하는 용액, 예컨대, 케토롤락 및 페닐에프린으로 이루어진 액체 관주 용액을 안구내로 투여함으로써 안과의 외과적 처치 이후의 수술 후 염증성 병태를 억제시키는 방법을 제공한다. The present invention provides methods for inhibiting postoperative inflammatory conditions following ophthalmologic surgical procedures by administering intraocularly during an ophthalmologic surgical procedure a solution including a nonsteroidal anti-inflammatory agent and an alpha-1 adrenergic mydriatic agent, such as a liquid irrigation solution of ketorolac and phenylephrine.